Tensions Between Teaching Sexuality Education and Neoliberal Policy Reform in Quebec’s Professional Competencies for Beginning Teachers - Parker, Dan; McGray, Robert (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2015)
This research draws into question the effects that neoliberal policy reforms — with an emphasis on individual and measurable “competencies” — has on new teachers teaching sexuality education in Quebec. While we examine professional competencies that teachers can use to define their mandate for teaching sexuality education as a beginning professional, we also detail the ways in which the competencies constrain pedagogical practice. Our argument is that while there are avenues for teachers to use the professional competencies for sexuality education, neoliberal reforms atomize teachers in a search for accountability. As a result, for fear of generating controversy, potentially contentious issues like sexuality education are not readily addressed. This atomization restricts both teachers and the field — the policy circumscribes sexuality education as personal rather than cultural. As such, we are left impotent to address cultural issues of sexuality education.